2014
DOI: 10.1177/1470320314562060
|View full text |Cite
|
Sign up to set email alerts
|

Role of MiR-30a in cardiomyocyte autophagy induced by Angiotensin II

Abstract: Objective: The aim of this study was to investigate whether MiR-30a regulates autophagy by regulating the Beclin-1 protein, which is the marker for autophagosomes during myocardial injury, when induced by angiotensin II (Ang II). Methods: We randomly assigned 20 rats into two equal groups: Control group and Ang II group. We detected the expression of MiR-30a by quantitative real-time polymerase chain reaction (RT-PCR), and we employed western blotting to detect the protein expression of Beclin-1. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Treatment of cardiomyocytes with miR-30a mimics decrease in the cardiomyocyte surface area and attenuates the Ang II-induced upregulation of hypertrophy-related genes ANP and β-MHC in vitro (Pan et al 2013). Consistent with the above study, Ang II-induced cardiomyocyte autophagy may correlate with the downregulation of miR-30a through upregulation of the Beclin-1 protein in vivo (Huang et al 2015a). Taken together, several miRNAs are associated with Ang II-induced pathological cardiac hypertrophy and autophagy, and this would provide a novel strategy for the management of cardiac hypertrophy.…”
Section: Effects Of Microrna In Ang Ii-induced Autophagysupporting
confidence: 81%
“…Treatment of cardiomyocytes with miR-30a mimics decrease in the cardiomyocyte surface area and attenuates the Ang II-induced upregulation of hypertrophy-related genes ANP and β-MHC in vitro (Pan et al 2013). Consistent with the above study, Ang II-induced cardiomyocyte autophagy may correlate with the downregulation of miR-30a through upregulation of the Beclin-1 protein in vivo (Huang et al 2015a). Taken together, several miRNAs are associated with Ang II-induced pathological cardiac hypertrophy and autophagy, and this would provide a novel strategy for the management of cardiac hypertrophy.…”
Section: Effects Of Microrna In Ang Ii-induced Autophagysupporting
confidence: 81%
“…Previous studies have shown the role of miR-30a in autophagy by regulating Becn1 (Chen et al, 2015; Huang et al, 2015; Wang et al, 2003). Upon examination of miR-30a binding affinity with 3′ UTR region of mouse Becn1 using various analyses tools (microRNA.org, TargetScan, miRWalk etc as described in Materials and Methods), we observed binding affinity of miR-30a with mouse Becn1 3′UTR region (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…However, due to abnormal expression of myocardial enzyme in various cardiac diseases and low specificity, it is of great significance to find markers for diagnosing ACOP cardiac injury. MircoRNA is a kind of small molecule non-coding RNA; previous studies have shown that miR-30a participates in the occurrence and development of cardiovascular diseases, and plays an important role in myocardial function, myocardial cell necrosis and apoptosis by regulating its target genes ( 15 ), proving that miR-30a is abnormally expressed in blood of patients with myocardial infarction ( 16 ). At present, the treatment of ACOP includes giving high concentration and high flow of oxygen, ventilation support and detection of abnormal heart rate ( 17 ).…”
Section: Discussionmentioning
confidence: 99%